The role of financial slack, employee creative self-efficacy and learning orientation in innovation and organizational performance - Khoa T. Tran; Phuong V. Nguyen; Linh M. Nguyen (Administrative Sciences, 2018)
Organizational performance development and financial slack have drawn extensive attention in management research. Recent studies have indicated that financial slack has a positive effect on innovation outcomes and organizational performance. However, some other studies have proposed adverse effects. This paper aimed to explore the causal linkages between employee creative self-efficacy, learning orientation, financial slack, innovation outcomes and organizational performance. It also examined the influence of innovation performance and creative self-efficacy as mediating variables in the connection between learning orientation and organizational performance. By doing so, we used a structural equation modelling (SEM) method to test the model using data from 267 small medium enterprises (SMEs) in Vietnam. The findings illustrated that SMEs had not utilized financial slack to invest in innovation activities and improve firm performance. Furthermore, the results indicated that learning orientation had both direct and indirect impacts on innovation and firm performance. It is worth noting that employee creative self-efficacy had a positive effect on innovation performance. The findings also verified a statistically significant association between innovation and organizational performance. Finally, the results provided some managerial implications to stimulate employees to work creatively and improve innovation outcomes for sustainable development.
Keywords: 350; creative self-efficacy; learning orientation; financial slack; innovation outcomes; organizational performance